Identities and social change in Britain since 1940 the politics of method - Savage, Michael, 1959- (Oxford : Oxford University Press, 2010)
This title examines how, between 1940 and 1970 British society was marked by the imprint of the academic social sciences in profound ways which have an enduring legacy on how we see ourselves. It focuses on how interview methods and sample surveys eclipsed literature and the community study as a means of understanding ordinary life.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Social change -- Great Britain -- History -- 20th century; Great Britain -- Social conditions -- 1945-; Great Britain -- Economic conditions -- 1945-; Great Britain -- Politics and government -- 1945-